Characterisation of thin boron-doped diamond films using Raman spectroscopy and chemometrics. Issue 5 (10th January 2019) - Knittel, Peter; Stach, Robert; Yoshikawa, Taro; Kirste, Lutz; Mizaikoff, Boris; Kranz, Christine; Nebel, Christoph E.
Abstract : A non-destructive chemometric method to determine thickness and boron concentration of as-deposited, thin, heavily doped diamond films by Raman microscopy. Abstract : Diamond coatings are characterised by outstanding mechanical and chemical robustness and hence, thin diamond layers doped with boron are particularly interesting for transparent electrodes, e.g., for spectroelectrochemical applications. In this study, we present a non-destructive chemometric method to determine thickness and boron concentration of as-deposited heavily doped diamond films on silicon substrates, which may be used, e.g., as electroactive infrared transparent windows. Using partial least-squares regression, we readily predicted these parameters with high accuracy from Raman spectra after calibration with a set of diamond films, previously characterised by secondary ion mass spectrometry. Due to the Fano resonance caused by the boron incorporation into the diamond lattice, which is observable in the Raman spectrum, a precise determination of the boron concentration is possible. In addition, for diamond films below the wavelength of the used Raman laser, we were able to determine the thickness of the as-grown films and gain information on the underlying substrate.